Growth and Yield Responses of White Cabbage Influenced by Vermicompost Tea and Vermicompost Tea Residue - Luu, Hai Thi Thuy; Le, Linh Truc; Huynh, Nga; Green, Iain D. (Journal of Agricultural Sciences (Belgrade), 2026)
White cabbage (Brassica oleracea var. capitata) is one of the oldest known vegetable crops and is commonly grown worldwide. Vermicompost tea (VCT) is considered a biofertiliser and is used in sustainable agriculture to promote crop yield and improve soil properties. This study was conducted to assess the efficacy of VCT and VCT residue (the solid material remaining after producing VCT) and their competency to partly replace inorganic fertilisers for the growth and yield of white cabbage under field conditions. The results showed that the use of VCT at an extraction ratio of 1:5 combined with 50% inorganic fertiliser significantly increased the cabbage head diameter and mean individual weight at harvest compared to the 100% inorganic fertiliser treatment. Noticeably, the application of VCT in a 1:5 combination with VCT residue + 50% inorganic fertilisers and VCT in a 1:10 combination with VCT residue + 50% inorganic fertilisers showed the best performances among treatments, with significant increases in the 3-m2 plot yield of 24.7%, and 14.3%, respectively, compared to the treatment with 100% inorganic fertilisers. These results demonstrate that VCT combined with VCT residue can replace a substantial proportion of inorganic fertilisers in cabbage cultivation, thereby reducing reliance on these non-sustainable products while recycling waste materials in sustainable agriculture.
Keywords: Brassica oleracea var. capitata; cabbage; organic fertilisers; vermicompost tea; vermicompost tea residue